Measurement of Concentration of Some Heavy Elements in Soil and Some Vegetable Areas of the Capital Baghdad - Suha Abbas Ibrahim (Al-Mustansiriyah Journal of Science)
In this research, we collected 10 samples, 2 soil and 8 vegetables cultivated in orchard area allowing district agricultural land in Al-Khatib at a few distances from Kadhimiya district, and adjacent to the area Al-Huria samples are congested as in table 2 after the chemical digestion of the seamount by using the atomic absorption technique, we found the following results: The highest value of Cadmium in A5 sample was 0.0436 ppm and 0.026933 ppm, the highest value of Lead in the sample A1 (soil of Kadhimiya) was 0.07345 ppm average and the highest value of Brass in A2 was 1.1176 ppm and 0.1762 ppm. The highest value of Cadmium in B4 (Rashad) was 0.0514 ppm and 0.04303 ppm, and the highest value of Lead in B5 (Kirath) was 0.365 ppm and on average 0.2293 ppm, the value of Copper in B4 (Rashad) was 1.1491 ppm and 0.20185 ppm in seriously. The limits are permitted within the WHO (World Health Organization), and therefore, there is no contamination of these items in these regions A and B (allows bastinade Kadhimiya, Khatib) respectively.